1994
DOI: 10.1161/01.str.25.11.2138
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of transcranial Doppler-detected cerebral microemboli in patients referred for echocardiography.

Abstract: Transcranial Doppler can detect cerebral microemboli. These emboli may be a risk factor for embolic stroke. We studied the prevalence of microemboli in patients referred for echocardiography. Forty-two patients were evaluated. Patients were studied with continuous monitoring over one middle cerebral artery for 30 minutes, and the number of microemboli was recorded. Patients were divided into three groups, those with prosthetic heart valves (group A, n = 15), atrial fibrillation (group B, n = 14), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 22 publications
2
20
1
2
Order By: Relevance
“…However, several studies have found an association between HITS and increased risk of stroke. 14,17-19,25-29 Tong et al 19 found an association of HITS with known cardioembolic risk factors and history of prior stroke. In patients with carotid stenosis, HITS have been related to the degree of stenosis and associated with an increased risk of subsequent stroke or transient ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have found an association between HITS and increased risk of stroke. 14,17-19,25-29 Tong et al 19 found an association of HITS with known cardioembolic risk factors and history of prior stroke. In patients with carotid stenosis, HITS have been related to the degree of stenosis and associated with an increased risk of subsequent stroke or transient ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
“…Although the definition of HITS did not mention the temporal profile of the signal distribution, our own experience and previous reports [11][12] found HITS with an aleatory but homogeneous distribution over the monitoring time. MES have been detected in a variety of conditions, including prosthetic valve replacement, 13 high-grade carotid stenosis, 14 atrial fibrillation, 15 and acute cerebral ischemia, 16 but only a few studies 17,18 have reported MES in relation to intracerebral artery stenosis. MCA stenosis is a relatively rare disease in the Caucasian population, but it is strongly associated with a high rate of stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…4 TCD is a useful technique to detect air, platelet, thrombus, atheroma, and fat microemboli as short-duration HITS. [17][18][19][20] With the aid of TCD, HITS can be quantified and their source located during CABG, 1,11,13,[21][22][23][24] carotid endarterectomy, 25,26 angioplasty, 27 or angiography, 28 as well as in patients with carotid stenosis, 29 -32 prosthetic cardiac valves, 29,[32][33][34][35][36] atrial fibrillation, 36 myocardial infarction, and stroke. [37][38][39] However, the clinical sequelae of HITS detected by TCD are still under debate.…”
mentioning
confidence: 99%